Geofluids developments in microthermometry, spectroscopy, thermodynamics, and stable isotopes - Hurai, Vratislav; Huraiová, Monika; Slobodník, Marek; Thomas, Rainer (Elsevier, 2015)
Geofluids: Developments in Microthermometry, Spectroscopy, Thermodynamics, and Stable Isotopes is the definitive source on paleofluids and the migration of hydrocarbons in sedimentary basins-ideal for researchers in oil and gas exploration. There's been a rapid development of new non-destructive analytical methods and interdisciplinary research that makes it difficult to find a single source of content on the subject of geofluids. Geoscience researchers commonly use multiple tools to interpret geologic problems, particularly if the problems involve fluid-rock interaction
Includes bibliographical references and index
Keywords: SCIENCE / Earth Sciences / Geography; SCIENCE / Earth Sciences / Geology; Fluid dynamics; Groundwater; Hydrogeology; Crust of the Earth; Fluids / Migration; Geografie; Geologie; Geowissenschaften; Fluids -- Migration; Fluid-Fels-System; Stabiles Isotop; Isotopengeochemie; Chemische Analyse; Geothermobarometrie; Fluideinschluss; Geochemie; Datenauswertung; Flüssigkeitseinschluss; Phase -- Thermodynamik; Geothermometrie; Fluid; Fluid-Feststoff-System; Hydrogeologie